The Implementation of Flip Learning Method in Learning English at Senior High School Students - Zuldilla Septi Rahayu; Havid Ardi (Universitas Negeri Padang, 2022)
Flip learning is a form of blended learning (through face-to-face and virtual/online interactions) that combines synchronous and asynchronous independent learning. Synchronous learning usually occurs in real time in the classroom. Asynchronous learning is learning that is more independent outside the classroom. This study investigated the implementation of Flip Learning Method in teaching English. This study aims to find out does the teacher have implemented all the steps of flip learning method in learning English subject at SMA N 16 Padang. The data in this study were the results of the observation checklist and interview. The sources of data are video recorded of learning activity, WhatsApp, and Google Classroom. The data in this study were obtained using an observation checklist and interview guide. In this study there are four steps of implementing Flip Learning Method, namely before class begins, beginning of class, during class, and after class. In this study found that in before class begin, from a total 4 steps that contained in the observation checklist, only 2 steps have been implemented and 2 steps have not been implemented. For beginning of class, there are 2 steps and both are not implemented. For during class, there are 6 steps and all the steps have been done. And in the after-class, there is 1 step and this step has also been caried out. Based on this research, the researcher found that the implementation of flip learning method in the English subject at SMA N 16 Padang is not perfect.